Bullous Type 2 Lepra Reaction: A Rare and Significant Case Report - Hrithik Dakssesh Putta Nagarajan; Balakrishnan Kamaraj; Keerthivasan Selvanathan; Pruthvi Raj Kukunoor; Katta Manichandana; Katta Manideep; Biki Kumar Sah (Clinical Case Reports)
ABSTRACT Bullous type 2 lepra reactions are a rare initial presentation in leprosy that can complicate the disease with vesiculo‐bullous lesions. Early recognition and differentiation from other bullous disorders are critical for timely corticosteroid and multidrug therapy initiation to improve patient outcomes.